Penerapan IPTEK Kelompok PKK Desa Dangdeur Melalui Pengembangan Produk Sabun Padat Berbasis Minyak Atsiri Serai Merah Sebagai Upaya Peningkatan Kesehatan di Era Pandemi Covid-19 - Rahmawida Putri; Nisrina Hikmawati; Diana Sylvia (Jurnal SOLMA, 2021)
Background: Dangdeur village has abundant red lemongrass resources but is only used as kitchen materials by the community. Utilization of red lemongrass through the development of solid soap products aims to apply science and technology to the PKK group Dangdeur village in an effort to improve health during the Covid-19 pandemic. This is because red lemongrass contains alkaloids, tannins, flavonoids, and saponins that are beneficial as antibacterial. Method: This activity was attended by 25 PKK members on the first day and 30 PKK members on the second day with the stage of activities that began with counseling activities to improve public understanding in preventing the spread of the Covid-19 virus. Activities continued by processing red lemongrass into essential oils through a simple distillation process as an active ingredient in the development of solid soap products. And ended with the process of processing solid soap based on red lemongrass essential oil and the process of packaging soap to be interesting. The activity is closed by providing an evaluation of the process and the results of the service through the provision of questionnaires to partners. Results: People's understanding and skills in processing red lemongrass into essential oils, tools and materials and the process of making solid soap increased by 16.3%. Conclusion: The implementation of this community activity can help the community in utilizing herbal plants efficacious in the field of health as an effort to improve public health during the Covid-19 pandemic.